اعمال السيادة في ظل التطور التشريعي والقضائي في النظم المقارنة - العاني وسام صبار (Journal of Legal Sciences, 2020)
Acts of sovereignty means a group of acts performed by the executive authority, and shall not be subjected to the Judicial review by cancelation or compensation. Therefore, the acts of sovereignty - in such situation - considered to be out of legitimacy, and have been subjected to a great criticism by the French jurisprudence and then the Egyptian jurisprudence on the bias that the executive authority may employ the idea of acts of sovereignty in its favor, by performing whatever acts in the form of sovereignty, that shall be sufficient to make such acts out of legitimacy and law rules, in such case the judiciary shall not have the right of cassation, or contestations against such acts nor the seeks of compensation because of the damages resulted by such acts. Hence the seriousness of this theory appears which was created by the French judiciary. The idea of acts of sovereignty has played an important role in the conflict of the state authorities, and highlighted the importance of the legitimacy principle, and the legality of the state through theJurisprudential disagreements and discussions. Although that such theory was created in the French administrative judiciary, it could be found in other judicial systems of other countries such as Egypt and Iraq. And although the weakness of such theory, it could be alive until now, furthermore, it could have a power in many common legal systems. Because of the absence of the administrative judiciary in Iraq, the researchers could not practice such theory with its activities. As the second amendment law was issued of the law of council of state No.(106) in 1989, announcing the administrative judiciary by establishing a court (for the first time) in which the cassation in the trueness of the orders and decisions issued by the employees and administrative bodies shall be performed.